Security and software for cybercafes - Adomi (Information Science Reference, 2008)
"This Book provides relevant theoretical frameworks and current empirical research findings on the security measures and software necessary for cybercafes, offering information technology professionals, scholars, researchers, and educators detailed knowledge and understanding of this innovative and leading-edge issue, both in industrialized and developing countries"--Provided by publisher.